In vitro fermentation of Gracilaria lemaneiformis sulfated polysaccharides and its agaro-oligosaccharides by human fecal inocula and its impact on microbiota - Zhang, Xiao; Aweya, Jude Juventus; Huang, Zong-Xun; Kang, Zhuo-Ying; Bai, Zi-Hao; Li, Kun-Huan; He, Xiao-Tong; Liu, Yang; Chen, Xian-Qiang; Cheong, Kit-Leong (Carbohydrate polymers, 2020)
•Sulfated polysaccharide (GLP) and agaro-oligosaccharide (GLO) from G. lemaneiformis were fermented in vitro by human fecal.•GLP and GLO altered intestinal microbes and promoted short chain fatty acids production.•The molecular weight and intrinsic viscosity of GLP were decreased after gut microbiota fermentation.•GLP and GLO are potentially useful as sources of prebiotics in functional foods. The fermentation behaviour of sulfated polysaccharides (GLP) and their agaro-oligosaccharides (GLO) derived from Gracilaria lemaneiformis were examined. During in vitro fermentation, GLP and GLO increased the concentrations of short chain fatty acids (SCFAs) and modulated the composition and diversity of gut microorganisms compared with control groups. GLP increased the abundance of Bacteroidetes and decreased the abundance of Firmicutes, while GLO increased the abundance of Firmicutes and Actinobacteria. Moreover, the abundances of potential pathogenic bacteria were reduced. Molecular weight and intrinsic viscosity of GLP decreased significantly from 2.15 × 105 to 1.22 × 105 Da, 374.45–113.91 mL/g, respectively. Furthermore, GLP was degraded into smaller degree of polymerization of oligosaccharides, with no significant change observed in GLO. Overall, this study revealed GLP and GLO could be beneficial for gastrointestinal tract by producing SCFAs and modulating intestinal microbes, indicating GLP and GLO are potentially sources of prebiotics in functional foods.